New Generation Package PrimePACKTM3+ Improving the Performance of IGBT5 Module - ZHAO Zhenbo; Wilhelm Rusche; Andre R.Stegner (Kongzhi Yu Xinxi Jishu)
To fully implement the feature of higher junction temperature for IGBT5, a new generation PrimePACKTM3+ module with the latest .XT technology and innovative design method is used to increase output current capability comparing with PrimePACKTM3 with the same size and footprint. The second AC bus bar and AC output power terminals are added in the new package. Almost 30% higher current capability of IGBT5 in comparison to IGBT4 is achieved by the package improvement, even 25℃ increase of the highest permitted operational temperature for IGBT5 is reached compared with PrimePACKTM3, and the highest point temperature inside module could be effectively lower. Based on the same package footprint, to integrate higher current density of IGBT5 chip, trade-off curve between losses and softness could be optimized to get lower overshoot voltage within the safe working area of RBSOA in the datasheet.